1027. TROPAEOLUM PENTAPHYLLUM subsp. MEGAPETALUM: Tropaeolaceae. (13th June 2022) - Hind, Nicholas; Moore, Richard; King, Christabel
Summary: Tropaeolum pentaphyllum Lam. subsp. megapetalum (Buchenau) Sparre (Tropaeolaceae) is described and illustrated; the subspecies is endemic to Bolivia, but is relatively widespread in montane areas between 1900 and 3100 m. Cultivation and related notes are provided. The presence of thread‐like pollenkitt has been observed amongst the pollen in dehiscing anthers of T. pentaphyllum subsp. megapetalum, T. pentaphyllum subsp. pentaphyllum, T. austropurpureum (J. M. Watson & A. R. Flores) J. M. Watson & A. R. Flores, T. brachyceras Hook. & Arn., T. tricolor Sweet, a proposed hybrid (originating at Kew), T. tricolor  ×  brachyceras and T. majus L., and in herbarium material of T. minus L. and T. speciosum Poepp. & Endl., although viscin‐like threads have never been reported in Tropaeolum before. The likelihood that this is connected with the ornithophilous pollination biology is discussed as is the potential for further research. The distinction of the subspecies is discussed in relation to the other two subspecies. A perspective on the Tropaeolaceae is provided, and a brief history of Tropaeolum outlined. Tropaeolum sect. Chilensia subsect. Chymocarpus (within which T. pentaphyllum is placed) is now validated after previous attempts failed, and a new combination provided.